DEPENDABILITY OF TECHNOLOGY IN ADDRESSING ILLUSIONARY TENDENCIES IN COCOA PRODUCTION IN NIGERIA: A CASE STUDY OF OGUN STATE. (FUDMA JOURNAL OF SCIENCES, 2023)
Productivity and efficiency require accurate measurements of inputs such as input per unit of land in crop production. However, indigenous methods rather than standardized scientific techniques are usually employed in determining measures in Africa, particularly in Nigeria. This study examined the relevance of Global Positioning System (GPS) technology in cocoa farm size determination in Ogun State, Nigeria. A total of 150 respondents were sampled through a multistage sampling technique. The data obtained were analyzed using descriptive analysis, student-t test statistic, budgetary and Probit regression techniques. Results revealed that predominantly male farmers (87.9%) with age group of 51 - 60 (39.4%) were more involved in cocoa production. Also, average annual cocoa revenue and net income of the respondents were N103,469.39 and N54,310.34 per hectare respectively. Farm size as determined by farmers was significantly different from that measured by GPS (p
Keywords: farmers, cocoa, illusion, indigenous knowledge, GPS